2022
DOI: 10.2807/1560-7917.es.2022.27.39.2100618
|View full text |Cite|
|
Sign up to set email alerts
|

Use of healthcare reimbursement data to monitor bacterial sexually transmitted infection testing in France, 2006 to 2020

Abstract: Background Diagnoses of bacterial sexually transmitted infections (STIs) have increased in France since the 2000s. The main strategy to control STI transmission is recommending/facilitating access to condom use, testing, and antibiotic treatments. Aim This study analyses the evolution of STI testing in the private sector in France from 2006 to 2020. Methods N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…While our results rely on self-reported data, they are substantiated by laboratory data from Sweden, indicating a decrease in STI tests in 2020 versus 2019 of up to 25% varying by region [20]. Similar reductions occurred in HIV/STI tests in Belgium [21], France [22] and the wider european region [6].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While our results rely on self-reported data, they are substantiated by laboratory data from Sweden, indicating a decrease in STI tests in 2020 versus 2019 of up to 25% varying by region [20]. Similar reductions occurred in HIV/STI tests in Belgium [21], France [22] and the wider european region [6].…”
Section: Discussionsupporting
confidence: 71%
“…Possibly, cis-women in our study were also less affected if using alternative contraceptives in steady partnerships, reducing their need for condoms and opportunistic STI testing. French data also showed a greater reduction in STI testing for men than women during the pandemic [22]. Pre-pandemic evidence suggested that sexual and gender minorities faced barriers accessing HIV/STI testing and youth clinics in Sweden, indicating pre-existing inequities [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…51 Similarly, a study analyzing the STI screening data from the French national health database revealed a 37% decrease in the total number of STI screenings in April 2020 during the first wave of COVID-19 compared to March 2020, with a 32% decrease in syphilis testing. 52 Redeployment of essential staff was an important reason for the decreased supply of STI care in the COVID-19 era. Before COVID-19, contact tracing was an essential component in many STD monitoring and management strategies.…”
Section: Reduced Volume Of Clinic Visits and Testingmentioning
confidence: 99%
“… 51 Similarly, a study analyzing the STI screening data from the French national health database revealed a 37% decrease in the total number of STI screenings in April 2020 during the first wave of COVID-19 compared to March 2020, with a 32% decrease in syphilis testing. 52 …”
Section: Syphilis-related Medical Resources and Health-seeking Choice...mentioning
confidence: 99%
See 1 more Smart Citation